Simple Nutrition Screening Tool (SNST) in Nutritional Assessment as a Risk Factor for Cardiovascular Disease in the Elderly - Ratna Indriawati; Muhammad Rivai Aziz (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
The elderly with nutritional disorders requires healing complications in their disease. Nutrient intake for the elderly with illness is needed for the healing process and to prevent further complications. One of the biggest factors of mortality in old age is non-communicable diseases, namely cardiovascular disease. This study aims to determine the relationship between the Simple Nutritional Screening Tool (SNST) in nutritional assessment and risk factors for cardiovascular disease in the elderly. This study used a cross-sectional method which was conducted for three months with a total of 51 respondents. Primary data collection was done by an interview with a questionnaire guide. Anthropometric and biochemical data from medical records. The results showed that SNST data showed that 92.20% were not at risk of malnutrition, and 7.80% were at risk of malnutrition. Chi-Square test between body mass index (BMI), blood pressure, LDL, HDL, blood sugar, smoking behavior, food intake, diet, and eating frequency as cardiovascular risk factors with SNST was not significant (p>0.05). The research concludes that there is no relationship between SNST and body mass index (BMI), blood pressure, LDL, HDL, blood sugar, smoking behavior, food intake, eating patterns, and eating frequency as cardiovascular risk factors in the elderly.